Ordem e justiça social : a igreja católica e o projeto de reforma agrária do Governo João Goulart (1961-64) - Bastos, Guido Coelho de Magalhães (2008)
The social matter that emerges from the contradictions inherent to capitalism, marked out by the deepened of the inequalities between the social classes became an object of attention and analysis by the Holy See, starting with Leão XIII. With the advances of communism and capitalism social conflicts, the Brazilian Catholic Church, in the decades of the fifties and the sixties, starts to approach to the poor class, a movement coming from its progressive wing, and found and opening during the process of articulation of the Vatican Council II (1962-65). Aiming at contributing for a better comprehension of the Catholic Church´s role (not homogeneous, and with plenty of tendencies) in this scenario, this essay will analyze the courses and speeches of two catholic periods, the first being called Brazil Urgent (BU, 1963-64) and the second Revista Eclesiástica Brasileira (REB, 1961-64), highlighting its approaches and distances, mainly when it comes to the Agrarian Reform during the process of political and social radicalization between the right and left political wings during the government of João Goulart (1961-64). Aiming at enrinching this study even more, information from an interview given by Frei Carlos Josaphat will be presented. He is the founder and former director of Brasil, Urgente . How did Brasil, Urgente and the Revista Eclesiastica Brasileira received the information from the encyclical of João XXIII (1958-63)? How did Brasil, Urgente and the Revista Eclesiastica Brasileira take position before president Goulart and his Agrarian Reform project? What were the proposals of Brasil Urgente and the Revista Eclesiástica Brasileria concerning the Agrarian Reform in Brazil? This matter and others ones will be dealt here.